PENINGKATAN KUALITAS WARNA DAN PERTUMBUHAN IKAN ALBINO TIGER BARB (Puntius tetrazona) DENGAN PEMBERIAN PAKAN YANG MENGANDUNG TEPUNG UDANG REBON - Nur Addini; Niken Ayu Pamukas; Mulyadi Mulyadi; Sukarman Sukarman (Berkala Perikanan Terubuk, 2017)
This  research  was  conducted  from  7th   of  March  to  16th   April  2017  at Research Center and Ornamental Fish Aquaculture (BRBIH), Depok - West Java. The objective of the research was to investigate the best of krill meal in fish meal and to increase color qualit y and growth of albino tiger barb (Puntius tetrazona). The method used was experimental method with Completely Randomized Design, with 4 treatment and 3 replications, ie 0%, 10%, 20%, 30% respectively. The fish were reared in aquarium with size of 40 cm x 30 cm x 30 cm (15 liters of water) with  density  of  10  fish/aquaria.  Fish  was  fed  3  times  a  day by means  of  at satiation.  Color sampling was done at the beginning  and the end of the study, while for growth sampling was done in the beginning and then every 10 days. The results showed that 30% krill meal gave the best color quality effect with L* =56.53, C = 16.60, H = 79.83, and absolute growth weight 0.68 g, absolute growth length 1.02 cm, specific growth rate 2.13% respectively.